Alpha generation’s social media use: sociocultural influences and emotional intelligence - Lidia Piccerillo; Alessia Tescione; Alice Iannaccone; Simone Digennaro (International Journal of Adolescence and Youth)
Preadolescence, a critical developmental stage, is increasingly influenced by social media, blending physical and virtual experiences. Generation Alpha, born entirely in the digital age, is particularly impacted as technology shapes their growing, learning and social interactions. Social media’s emphasis on appearance affects body image and emotional intelligence, yet research has primarily focused on adolescents and girls, leaving gaps for preadolescents. This study involved 721 preadolescents aged 10–15 years (M = 12.1, SD = 0.87), with 45.7% boys (N = 341) and 52.7% girls (N = 380). Structural equation modelling examined three hypotheses: (H1) increased social media use correlates with addiction, (H2) promotes sociocultural appearance ideals, and (H3) negatively affects emotional intelligence. Results showed social media use significantly predicted addiction (β = .47, p < .001), reinforced appearance ideals (β = .39, p < .001), and was inversely associated with emotional intelligence (β = −.22, p < .01). Findings highlight both risks and sociocultural influences of social media, particularly on younger users.